Enhancing privacy and traceability of public health insurance claim system using blockchain technology - Alamsyah, Andry; Setiawan, I. Putu Sadhu (Frontiers in Blockchain, 2025)
IntroductionThe insurance industry has evolved into a global multi-billion-dollar sector, with health insurance gaining prominence due to escalating healthcare costs. This rapid expansion brings heightened risks, including data breaches, fraud, and difficulties in safeguarding sensitive policyholder information. Indonesia’s National Health Insurance (NHI)—one of the largest national insurance programs worldwide—covers over 200 million citizens, aiming to provide universal healthcare. However, this extensive coverage raises substantial concerns about data privacy and traceability, particularly during the claim process, as policyholders currently have limited control over and insight into how their data is accessed and used.MethodsTo address these challenges, we propose a blockchain-based model designed to enhance policyholders’ private control over data access and improve traceability throughout the NHI claim process. Our approach employs three complementary architectures—functional, logical, and physical—to guide system implementation. The functional architecture is illustrated via a use case diagram that outlines the roles and actions of each participant. The logical architecture employs Business Process Model and Notation (BPMN) diagrams to depict the revised process flow and data movement, while also incorporating a layered design concept. The physical data architecture provides a class diagram detailing data structures and actor relationships. A proof-of-concept prototype was developed to demonstrate the core functionalities of the new system.ResultsBy integrating blockchain technology, our prototype ensures authorized access, bolsters data privacy, and maintains data integrity in the NHI claim workflow. The system’s layered design and use of smart contracts guarantee transparent, tamper-proof record-keeping, while parallelized processes in the logical architecture streamline claims handling. Initial tests of the prototype confirm the feasibility and robustness of the proposed solution, illustrating how blockchain can facilitate traceability and preserve confidentiality.DiscussionThe blockchain-based design addresses pressing concerns surrounding data security and accountability in large-scale health insurance systems. It allows policyholders to monitor and control their personal information, reducing the likelihood of unauthorized use. Furthermore, the transparent and immutable ledger enables stakeholders to verify data provenance and transactions, enhancing trust. Future work will focus on scalability, regulatory compliance, and integration with existing healthcare IT infrastructures to fully realize the benefits of blockchain in national health insurance programs.